Participatory rural appraisal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Participatory rural appraisal: practical experiences by J Nabasa, G Rutwara, F Walker and C Were 1995 52pp price UKL750 ISBN 0 85954 392 7